2017
DOI: 10.1590/1981-6723.07217
|View full text |Cite
|
Sign up to set email alerts
|

Utilização de ácido cítrico para a conservação pós-colheita de raízes de mandioca

Abstract: Resumo As raízes de mandioca de mesa minimamente processadas surgiram como uma alternativa para aumentar a vida útil pós-colheita do produto e disponibilizar um alimento mais prático e seguro para os consumidores. O Distrito Federal e entorno está se tornando um grande produtor e consumidor de mandioca de mesa. Dessa forma, objetivou-se determinar os efeitos de diferentes concentrações de ácido cítrico (0,5%, 1,0%, 1,5%, 2,0%, 2,5%) para a conservação de raízes de mandioca IAC 576-70 minimamente processadas, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 14 publications
1
5
0
5
Order By: Relevance
“…The value found for pH was (5.09) T3 (Table 4). This value (3.95 and 6.43) is close to that analyzed by Rinaldi et al (2017) using 1.0% citric acid in the post-harvest conservation of cassava.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The value found for pH was (5.09) T3 (Table 4). This value (3.95 and 6.43) is close to that analyzed by Rinaldi et al (2017) using 1.0% citric acid in the post-harvest conservation of cassava.…”
Section: Resultssupporting
confidence: 84%
“…Rinaldi et al (2015) when analyzing the effect of freezing on cassava roots found pH values between 6.09 and 6.47 when frozen at -18 °C, results similar to those found at T1, T2 and T4 (Table 4). According to Rinaldi et al (2017), the pH is a factor that has great importance in food conservation, since it can act as a barrier to the development of microorganisms, so it is ideal that the pH should not exceed 4.5.…”
Section: Resultsmentioning
confidence: 99%
“…Although there was no significant difference in texture data during storage, all treatments had a more pronounced reduction during the first seven days of storage (Table 2). Rinaldi et al (2017b) also did not observe a significant difference in the texture of cassava roots of the same cultivar. The roots were immersed in water with different concentrations of citric acid after minimal processing, with texture values ranging between 39.66 N and 16.71 N. The storage temperature was set at 30 °C for 35 days.…”
Section: Ss/ta Ratio Texture and Fresh Weight Lossmentioning
confidence: 65%
“…After seven days, only the product subjected to the 200 μm LDPE package with and without vacuum did not show significant variation in a* values until the end of storage. These values are responsible for regulating chlorophyll degradation: when a* is positive, the product has a reddish color; when a * is negative, the product is green (Rinaldi et al, 2017b).…”
Section: Colormentioning
confidence: 99%
“…It is a viable alternative to reduce post-harvest losses, minimal root processing and packaging in vacuum packaging still on rural property or in supermarkets, since there is currently a growth in this market, since consumers seek products that, in addition, have practicality (Menezes, 2012). Rinaldi et al, (2017) describe that minimal root processing involves stages of selection, classification, peeling, cutting, sanitization, rinsing, packaging, and storage. The shelf life of these minimally processed products should be sufficient to ensure the quality of food, in addition to providing food safety to the consumer (Rinaldi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%